Integrating Science-Based Co-management, Partnerships, Participatory Processes and Stewardship Incentives to Improve the Performance of Small-Scale Fisheries - Karr, Kendra A.; Fujita, Rod; Carcamo, Ramon; Epstein, Lawrence; Foley, James R.; Fraire-Cervantes, José A.; Gongora, Mauro; Gonzalez-Cuellar, Ollin T.; Granados-Dieseldorff, Pablo; Guirjen, Julius; Weaver, Amy H.; Licón-González, Héctor; et al. (Frontiers in Marine Science, 2017)
Small scale fisheries are critically important for the provision of food security, livelihoods, and economic development for billions of people. Yet, most of these fisheries appear to not be achieving either fisheries or conservation goals, with respect to creating healthier oceans that support more fish, feed more people and improve livelihoods. Research and practical experience have elucidated many insights into how to improve the performance of small-scale fisheries. Here, we present lessons learned from five case studies of small-scale fisheries in Cuba, Mexico, the Philippines, and Belize. The major lessons that arise from these cases are: 1) participatory processes empower fishers, increase compliance, and support integration of local and scientific knowledge; 2) partnership across sectors improves communication and community buy-in; 3) scientific analysis can lead fishery reform and be directly applicable to co-management structures. These case studies suggest that a fully integrated approach that implements a participatory process to generate a scientific basis for fishery management (e.g., data collection, analysis, design) and to design management measures among stakeholders will increase the probability that small-scale fisheries will implement science-based management and improve their performance.